Test Hybrid PV System Performance Against Load Variations - Aripriharta, Aripriharta; Amin, Muhammad Adib; Sujito, Sujito; Faiz, Mohamad Rodhi; Bagaskoro, Muhammad Cahyo; Susilo, Suhiro Wongso; Omar, Saodah (PTE FTK UIN Ar-Raniry, 2025)
The depletion of fossil fuels has driven significant changes in the global electricity system. Solar Power Plants (PLTS) as a renewable energy source have shown the potential to contribute up to 25% of global electricity generation by 2050. The electricity system often experiences disturbances that can affect its performance and reliability. This study examines the performance of a 1.2 kW hybrid PV system under various load conditions. The system was tested with load variations of 2%, 7%, 22%, and 26% to assess its efficiency and performance. Despite a slight voltage drop of 4V Vac (-1.82%) at higher loads, the hybrid PV system consistently maintained a voltage range of 216-220V Vac, which meets the standard requirements. The system demonstrated high efficiency, averaging over 95%, with a peak efficiency reaching 98.5% at 2% load. These results confirm the effectiveness, safety, and reliability of the system under various load conditions. The findings are based on direct testing and measurements of a 1.2 kW hybrid PV system to evaluate the impact of load variations on its performance. The 1.2 kW hybrid PV system has been proven to be effective, safe and reliable in the face of load variations. These findings support the potential implementation of hybrid PV systems as a future renewable energy solution in the electricity sector